(3GdTaG HJYQja Mbhb GdeUWais - (3YjGV Hf ehSi Hf YjGV Hf YeQhf GdjMUHj GdSHJj, CHh GdaVd,J (B544 (3g` s
(3ChdgG (B:s
(3GdMeO GdefaQO HGSeg GdCSei CeG HYO aEfc cQQJ Ydi GdSDGd ai eLehY jJVef GdJYQja HbOQ GdeUWai Ydjg GdUdGI hGdSdGe aGYde Cfc MedJfi ef Pdc CeQkG EeQG aHGOQJ Edi fcJ eSaQI s
(3BNQgG (B:s
(3jfJgi HfgGjI GdMOjK Yf MLR Gfg Udi Gddg Ydjg hSde s
(3fSNI CNQis
(3YdjgG JUMjMGJ hJbjjOGJs
(3Ydi GdhQbI GdChdi efgG JedcGJ ZjQ hGVMIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs